Morphological, karyological and palynological investigation of endemic Centaurea kurdica Reichardt from Turkey - Hayta, S.; Tasar, N.; Kiran, Y.; Cakilcioglu, U.; Bagci, E. (Taylor & Francis Ltd, 2016)
The purpose of this study was to determine the morphological, morphometrical, karyological and palynological features of the endemic Centaurea kurdica Reichardt species from East Anatolian region. Some morphological features of the species like morphology of capitula, involucra, involucral leaves (phyllaries) and achene have been investigated. The chromosome number of Centaurea kurdica was found as 2n = 18 and haploid karyotype formula 6m + 2sm + 1M. Metaphase chromosome length ranged from 5.81 to 3.91 mu m and the total haploid chromosome length was 41.09 mu m. The results of the light microscope investigation of pollen revealed that it is radially symmetrical, isopolar tricolporate and has spheroid-type pollen, and exine ornamentation was also determined as scabrate.
Keywords: Turkish endemic; Centaurea kurdica; karyotype; pollen